2012
DOI: 10.1007/s00228-012-1268-8
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding adverse drug reactions (ADRs) in patients exposed to antiplatelet plus serotonin reuptake inhibitor drugs: analysis of the French Spontaneous Reporting Database for a controversial ADR

Abstract: The data did not demonstrate any significant association between bleeding ADRs and exposure to SRI + antiplatelet agents versus antiplatelets alone. Considering other conflicting results, this risk should be kept in mind by physicians when treating patients with several risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This was demonstrated in the pharmacovigilance database study that showed no significant association between bleedings and exposure to SADs plus antiplatelet agents versus antiplatelet agents alone. 23 However, contrary to this thought, published studies have reported an increased bleeding risk associated with the addition of SADs to antiplatelet agents following myocardial infarction. 24 These differences may be attributed to the differences in the pharmacological properties of different SADs with regard to their affinity for the serotonin transporter, their inhibitory action on the CYP enzymes metabolising other drugs with bleeding risk (antiplatelets and anticoagulants), the dose of SADs used and their ability to compete for the CYP enzyme, at the substrate level.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This was demonstrated in the pharmacovigilance database study that showed no significant association between bleedings and exposure to SADs plus antiplatelet agents versus antiplatelet agents alone. 23 However, contrary to this thought, published studies have reported an increased bleeding risk associated with the addition of SADs to antiplatelet agents following myocardial infarction. 24 These differences may be attributed to the differences in the pharmacological properties of different SADs with regard to their affinity for the serotonin transporter, their inhibitory action on the CYP enzymes metabolising other drugs with bleeding risk (antiplatelets and anticoagulants), the dose of SADs used and their ability to compete for the CYP enzyme, at the substrate level.…”
Section: Discussionmentioning
confidence: 94%
“…Consequently, the additional effect of SADs on platelets in patients who are receiving long‐term potent antiplatelet therapy prior to surgery is negligible to have an impact on clinically important bleeding outcomes. This was demonstrated in the pharmacovigilance database study that showed no significant association between bleedings and exposure to SADs plus antiplatelet agents versus antiplatelet agents alone . However, contrary to this thought, published studies have reported an increased bleeding risk associated with the addition of SADs to antiplatelet agents following myocardial infarction .…”
Section: Discussionmentioning
confidence: 94%
“…461 Moreover, when used alongside APAs, perioperative use of SSRIs should be individualised. Although a French database analysis did not demonstrate any significant association between bleeding adverse drug reactions and exposure to SSRI and APAs versus APAs alone, 462 another database analysis found a high rate of adverse reactions of SSRIs related to drug-drug interactions. 463 Some SSRIs may interfere with warfarin metabolism and increase INR.…”
Section: Recommendationmentioning
confidence: 85%
“…The ENRICHD clinical trial and two following clinical outcome studies reported that concurrent SSRIs was associated with a significant reduced risk of death or recurrent MI as well as an increased risk in bleeding in clopidogrel treated patients [174176]. However, conflicting results were reported from several other studies [169, 177, 178], suggesting the necessity of further evaluation of the potential impact of SSRIs on clopidogrel antiplatelet treatment.…”
Section: Covariates That Affect Clopidogrel Dose/pk/pdmentioning
confidence: 99%